Weaving Mathematics and Culture into Danish Hearts - Chioda, Rachel; Killian, Julie (Ohio Journal of School Mathematics, 2019)
Woven from simple paper shapes, Danish Christmas hearts provide teachers with opportunities to engage their students in ethnomathematical inquiry. After providing cultural background and explaining how to create the hearts, the authors discuss an activity where students explore the symmetries present in the hearts and provide extensions applicable to students in grades 1-12+.